2012
DOI: 10.3109/10826084.2011.644379
|View full text |Cite
|
Sign up to set email alerts
|

The “Translators”: Engaging Former Drug Users as Key Research Staff to Design and Implement a Risk Reduction Program for Rural Cocaine Users

Abstract: This manuscript describes lessons learned in the development and implementation of a clinical behavioral trial to reduce sexual risk among African-American cocaine users in rural Arkansas, from the perspectives of a multidisciplinary investigative team and community staff members with a history as local drug users who served as “translators.” Recommendations for investigators doing community-based research with active substance users are provided in the following domains: (a) engaging the community during form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Core elements of Safety Counts were retained but session content was tailored to meet the study aims and the needs of the local cocaine-using population based on previous research in the area, 8,10 input from the CAB and community liaisons, 34 and focus groups conducted with members of the study population. 35 For example, we adapted content of Safety Counts to address primarily the risks of HIV and STI for non-injectors because of the project’s focus on cocaine users and prior research 8 documenting rarity of injection use amongst cocaine users in these rural counties.…”
Section: Methodsmentioning
confidence: 99%
“…Core elements of Safety Counts were retained but session content was tailored to meet the study aims and the needs of the local cocaine-using population based on previous research in the area, 8,10 input from the CAB and community liaisons, 34 and focus groups conducted with members of the study population. 35 For example, we adapted content of Safety Counts to address primarily the risks of HIV and STI for non-injectors because of the project’s focus on cocaine users and prior research 8 documenting rarity of injection use amongst cocaine users in these rural counties.…”
Section: Methodsmentioning
confidence: 99%
“…Core sexual risk reduction elements of Safety Counts were retained but session content was tailored to meet the study aims and the needs of the local cocaine-using population based on previous research in the area (21, 27), input from the CAB and community liaisons (28), and focus groups conducted with members of the study population (29). Both conditions included two 2-hour group sessions, two 60-minute individual sessions, two 2-to-3-hour community events, and two 40-minute follow-up individual sessions, occurring over four months.…”
Section: Methodsmentioning
confidence: 99%
“…Interviewers used Computer-Assisted Personal Interviewing (CAPI) technology to conduct the assessment; which took approximately 2.5 hours to complete with a 15-minute break. All interviewers were local residents of the study counties, and were self-identified as in recovery from cocaine abuse or dependence (28). After all 12-month follow-up assessments had been completed, semi-structured qualitative interviews with 36 randomly selected participants were conducted by study investigators using an interview guide.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews were conducted using Computer‐Assisted Personal Interviewing (CAPI) technology and took place in offices that were located centrally in each county and identified as an acceptable and trusted location by members of the research project's Community Advisory Board (CAB), a group of 10 men and women from the study community who met the study's inclusion criteria and served as advisors to the study during its conceptualization, development, and implementation . Recruiters and interviewers were residents of the study community who were selected in part because of their experience with and understanding of the needs and concerns of the study population . These individuals were employed full‐time by the research project and received extensive training in interviewing techniques to ensure the accuracy of the self‐report data.…”
Section: Methodsmentioning
confidence: 99%